Effects of standardizing kick plate position on track start biomechanics in elite swimmers - Cicenia, A.; Oster, C.; Mokha, G. (ISBS Proceedings Archive (Michigan), 2019)
Kick plate position in the track start is arbitrary but may influence performance. The purpose of this study was to investigate the influence of standardizing kick plate position based on shin length. 15 elite swimmers performed 3 starts at 3 kick plate positions (< shin length, shin length, and > shin length). Differences in reaction time (RT), block phase time, flight phase time, flight distance, underwater phase time, and time to the 15 m mark were examined between kick plate positions. Only RT was significantly different, (F(2,28)=4.713, p=.017). RT was lower when the kick plate distance was one shin`s length versus < shin length (0.173+0.034vs 0.194+0.061 sec) and > shin length (0.173+0.034 vs 0.195+0.047 sec), p<.05. Shin length may be an appropriate measure for kick plate position to enhance start performance.